Co-delivery of IOX1 and doxorubicin for antibody-independent cancer chemo-immunotherapy - Liu, Jing; Zhao, Zhihao; Qiu, Nasha; Zhou, Quan; Wang, Guowei; Jiang, Haiping; Piao, Ying; Zhou, Zhuxian; Tang, Jianbin; Shen, Youqing (Nature communications, 2021)
Anti-programmed cell death-1 (PD-1)/programmed cell death-ligand 1 (PD-L1) antibodies are currently used in the clinic to interupt the PD-1/PD-L1 immune checkpoint, which reverses T cell dysfunction/exhaustion and shows success in treating cancer. Here, we report a histone demethylase inhibitor, 5-carboxy-8-hydroxyquinoline (IOX1), which inhibits tumour histone demethylase Jumonji domain-containing 1A (JMJD1A) and thus downregulates its downstream β-catenin and subsequent PD-L1, providing an antibody-independent paradigm interrupting the PD-1/PD-L1 checkpoint. Synergistically, IOX1 inhibits cancer cells’ P-glycoproteins (P-gp) through the JMJD1A/β-catenin/P-gp pathway and greatly enhances doxorubicin (DOX)-induced immune-stimulatory immunogenic cell death. As a result, the IOX1 and DOX combination greatly promotes T cell infiltration and activity and significantly reduces tumour immunosuppressive factors. Their liposomal combination reduces the growth of various murine tumours, including subcutaneous, orthotopic, and lung metastasis tumours, and offers a long-term immunological memory function against tumour rechallenging. This work provides a small molecule-based potent cancer chemo-immunotherapy. Some chemotherapeutic drugs, such as doxorubicin, induce immunogenic cell death (ICD) and promote anti-tumor immune responses. Here the authors report that the histone demethylase inhibitor 5-carboxy-8-hydroxyquinoline (IOX1) reduces the expression of PD-L1 in cancer cells and enhances doxorubicin-induced ICD, promoting T cell infiltration and reducing tumor growth in preclinical models.